Menakar Potensi Perlindungan Hukum Mutiara Lombok Melalui Indikasi Geografis Dan Implikasinya: Sebuah Diagnosa Awal - Muh Ali Masnun (Faculty of Law, Universitas Pekalongan, 2017)
Lombok has Pearl attraction that has been known to foreign countries. The large potential is not yet widely realized to be given protection from legal aspects, so many countries that sell pearl products on behalf of / hijacked by the name of Mutiara Lombok. This research was conducted by normative juridical method. Using primary, secondary, and non-law material as the study. The results show that the potential of Lombok pearl law protection through geographical indication is very open. Forms of legal protection can be done in 2 ways, namely protection of preventive law and repressive law protection. The implications of Lombok Pearl protection through IG can at least be used as a) product marketing strategy at domestic and foreign trade; b) Provide added value to the product and improve the producer's welfare; c) Enhance the reputation of IG products in international trade; d) Equality of treatment as a result of promotion from abroad; and e) IG protection as one means to avoid fraudulent competition.Keywords: Legal Protection, Lombok Pearl